Features Of Water Seepage From The Retention Basins Of Irrigation Systems With Different Geological Structures - Orlinska, O. V.; Pikarenia, D. S.; Chushkina, I. V.; Maksymova, N. M.; Hapich, H.; Rudakov, L. M.; Roubík, H.; Rudakov, D.; Орлінська, О. В.; Пікареня, Д. С.; Максимова, Н. М. (AIP Publishing, 2022)
Topical applied and scientific problem concerning the evaluation of technical condition of retention basins of irrigation systems has been highlighted. The expediency of comprehensive use of geophysical methods of the natural pulsed electromagnetic field of the Earth as well as vertical electrical sounding to identify deformation zones of agricultural hydraulic structures and seepage techniques has been considered making it possible to determine parameters of the disturbed areas. It has been demonstrated that geological (inclusive of tectonic and hydrogeological) features of territorial structure and development are the factor of unsatisfactory technical condition of agricultural hydraulic systems of land-reclamation schemes turned out to be understudied during their design and construction. Localization of zones of water seepage losses to concentrate repair and restoration works within the most disturbed areas will help reduce significantly time and costs while improving the total efficiency of a hydraulic system operation. Hence, the measure emphasizes expediency of further use of the system of geophysical methods.
Keywords: Technical condition of hydraulic structures; Geophysical methods; Method of natural pulsed electromagnetic field of the Earth; Method of vertical electrical sounding; Seepage losses; Floodin